Corporate Choice Between Straight Debt And Convertible Debt In Malaysian Capital Market - Khaw, Lee Hwei (2008)
Malaysia capital market financing is developing along with the economy. It is aimed to meet the expanding financing needs. This study is interested to examine the firm specific characteristics that determine corporate choice between straight debt and convertible debt. 136 debt offerings are identified as the sample for the study, consisting of 107 straight debts and 27 convertible debts from year 2001 through 2007. Nine predetermined explanatory variables namely tax consideration, debt ratio, tangibility, firm size, growth opportunities, profitability, net operating cash flow (NOCF), interest coverage and board of listing are analysed by using binary logistic regression.Tax consideration is proxied by non debt tax shield and debt tax shield in which they are regressed separately. This study also introduces two additional explanatory variables i.e. interest coverage and board of listing. Initially, only two explanatory variables are found to be statistically significant i.e. debt ratio and growth opportunities, denoted by market-to-book ratio. Subsequently, the predictive quality of each equation is examined and found that there is an existence of multicollinearity. As a result, corrective analysis is presented. It illustrates that non debt tax shield; debt ratio and firm size are statistically significant. These results explain that tax consideration, debt ratio and firm size influence the corporate choice when deciding between straight debt and convertible debt. It is reported that firms with higher non debt tax shield are more likely to issue straight debt which is in contrast to the tradeoff theory. This shows that firms in Malaysia are also utilising the potential tax benefit from non debt item such as depreciation in addtion to tax deductible interest payment. Therefore, the empirical results from this study do not completely conform to the tradeoff theory. As for debt ratio, the finding is consistent with the implications of the financial distress and tax benefits hypotheses in which firms with higher debt ratio have a tendency to issue equity-like instrument, i.e. convertible debt. Conversely firms with lower debt ratio would issue straight debt. Results also show that firms with larger firm size are more likely to issue straight debt whereas firms with smaller firm size are more likely to issue convertible debt. This postulates a positive relation between firm size and debt which is also consistent with tradeoff theory since larger firms have been shown to have lower bankruptcy risk and relatively lower bankruptcy cost. In addition to the above results, it is discovered that non debt tax shield is more appropriate to represent tax consideration in the Malaysia capital market instead of debt tax shield.This study also introduces two additional explanatory variables i.e. interest coverage and board of listing of companies in Bursa Malaysia. However, both variables are insignificant, thus they could not explain the choice between straight debt and convertible debt.